Grief, Dōgen, and the Ethical Responsibilty to the Other Now Gone - Naoko Masuda (Journal of Applied Hermeneutics, 2023)
When a living other transforms into a recently-gone other, how does the relationship between two people change? After the sudden and unexpected loss of a lifelong friend, my grief not only focused on the physical loss and the loss of future opportunities together, but also raised questions about what this meant for the state of our relationship and for my own self-understanding. 13th century Japanese philosopher and Sōtō Zen founder Dōgen teaches that death is one with life and experienced every moment as life-and-death. For him, life is a series of ever-changing moments, and it is in this impermanence that one finds learning. Drawing on Gadamerian hermeneutics, I explore what it could mean to ethically relate to a beloved deceased other and how Dōgen’s teachings could help deepen understanding of grief as part of a continually evolving self-in-relation-with-other.